Tanaman sirih hijau (Piper betle UJI FITOKIMIA KANDUNGAN METABOLIT SEKUNDER DALAM DAUN SIRIH HIJAU (PIPER BETLE L.): Daun Sirih - Maharani, Adelya (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2023)
The green betel plant (Piper betle L.) is a type of plant that is widely used as herbal medicine in the community. This research aims to identify secondary metabolites and antioxidants in green betel leaves. Betel leaves (Piper betle L.) were extracted using the maceration method using 96% ethanol solvent. The thick extract obtained from maceration will be fractionated using the liquid-liquid method using distilled water and n-hexane (1:1). Secondary metabolite and antioxidant compound testing was carried out to determine the secondary metabolite content in simplicia, extracts and fractions of green betel leaves (Piper betle L.). The results of testing secondary metabolite compounds showed that green betel leaves were detected to contain alkaloids, flavonoids, phenolics, polyphenols and saponins. Based on antioxidant tests that have been carried out, betel leaf extract (Piper betle L.) contains antioxidants because it can neutralize free radical solutions.